1990
DOI: 10.1063/1.345645
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam plasma enhancement of oxidation in thin aluminum samples

Abstract: In order to gain an insight into the effects of a space environment on materials, thin aluminum samples were exposed to an oxygen plasma produced by an electron beam. Using Rutherford backscattering spectrometry the samples exposed to the oxygen plasma were compared to samples exposed to ordinary oxygen gas. The comparison revealed a considerable increase in oxygen diffusion in the samples exposed to the charged particle environment. The amount of oxygen diffusion depends on the duration of the plasma exposure. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…[8] Plasma oxidation of silicon has been used in integrated circuits to form high quality insulating oxide layers. Scheider et al [9] reported that aluminum samples oxidized in plasma showed significant increases in oxygen diffusion. Plasma-treated Cu-Al alloy also enhanced the reaction rate and caused selective oxidation.…”
Section: Introductionmentioning
confidence: 98%
“…[8] Plasma oxidation of silicon has been used in integrated circuits to form high quality insulating oxide layers. Scheider et al [9] reported that aluminum samples oxidized in plasma showed significant increases in oxygen diffusion. Plasma-treated Cu-Al alloy also enhanced the reaction rate and caused selective oxidation.…”
Section: Introductionmentioning
confidence: 98%